New insight into solar cell function.
Using light to produce either electricity or hydrogen, 'Dye-sensitised solar cells" (DSSCs) are currently the most efficient third-generation solar technology. Increases in their conversion efficiency through better understanding of how light absorption materials function will make them attractive for large scale deployment.
Keywords: Solar cell